2016
DOI: 10.1021/acs.chemmater.6b01994
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydrogen in Defining the n-Type Character of BiVO4 Photoanodes

Abstract: The roles of hydrogen impurity and oxygen vacancy defects on defining the conductivity, and hence photoelectrochemical (PEC) performance characteristics, of monoclinic scheelite bismuth vanadate (BiVO4) are investigated using a combination of experiment and theory. We find that elemental hydrogen is present as an impurity in as-synthesized BiVO4 and that increasing its concentration by annealing in H2 at temperatures up to 290 °C leads to near-complete elimination of majority carrier transport limitations, a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
157
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(174 citation statements)
references
References 57 publications
14
157
1
Order By: Relevance
“…The observed reduction of trap states density upon hydrogen treatment is in agreement with a recent report by Cooper et al, [29] where hydrogen-treated BiVO4 was found to exhibit a lower sub-bandgap photoluminescence intensity as compared to untreated BiVO4. The reduction in the number of trap states is also consistent with the increase in carrier lifetimes ( Figure 3 and Table 1), which in turn results in the cathodic shift of the onset potential in the photocurrent-voltage curve ( Figure 2).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The observed reduction of trap states density upon hydrogen treatment is in agreement with a recent report by Cooper et al, [29] where hydrogen-treated BiVO4 was found to exhibit a lower sub-bandgap photoluminescence intensity as compared to untreated BiVO4. The reduction in the number of trap states is also consistent with the increase in carrier lifetimes ( Figure 3 and Table 1), which in turn results in the cathodic shift of the onset potential in the photocurrent-voltage curve ( Figure 2).…”
Section: Resultssupporting
confidence: 92%
“…Thus, a hydrogen treatment appears to be a generally applicable strategy for improving the performance of BiVO4 photoanodes, as has also been reported by others. [24,29,38] Nevertheless, the main mechanism that causes the improvement of the PEC performance remains unclear.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[47,48] For the case of the pure BiVO 4 film, a broad peak near 700 nm is observed, which has been assigned to radiative recombination at bulk oxygen vacancy sites. [36] PL from the TiO 2 /BiVO 4 nanocomposite film is characterized by broad spectral emission.…”
Section: Defects and Photocarrier Recombinationmentioning
confidence: 99%